2021
DOI: 10.1001/jamanetworkopen.2021.21505
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Adjunctive Ultrasonography for Breast Cancer Detection Among Women Aged 40-49 Years With Varying Breast Density Undergoing Screening Mammography

Abstract: Key Points Question Does the performance of adjunctive ultrasonography for breast cancer detection among women undergoing screening mammography change according to breast tissue density? Findings In this secondary analysis of a randomized clinical trial, screening mammography alone demonstrated low sensitivity, whereas adjunctive ultrasonography improved sensitivity both in dense and nondense breasts. Meaning These findings sugge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
43
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(48 citation statements)
references
References 35 publications
(118 reference statements)
3
43
0
2
Order By: Relevance
“…For women who started receiving screening mammography annually at age 40, the 10-year cumulative probability of a false positive recall is 61% in Taiwan [ 17 ]. In Japan, the neighboring country of Taiwan, a previous study noted that 59.3% of cases were categorized as having dense breast tissues where the sensitivity of mammography or ultrasonography alone did not exceed 80% [ 18 ]. On average, when a woman starts the annual screening between 40 to 49 years of age, she may encounter one false positive mammogram per 10 years, and one in four women will receive one false positive biopsy [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…For women who started receiving screening mammography annually at age 40, the 10-year cumulative probability of a false positive recall is 61% in Taiwan [ 17 ]. In Japan, the neighboring country of Taiwan, a previous study noted that 59.3% of cases were categorized as having dense breast tissues where the sensitivity of mammography or ultrasonography alone did not exceed 80% [ 18 ]. On average, when a woman starts the annual screening between 40 to 49 years of age, she may encounter one false positive mammogram per 10 years, and one in four women will receive one false positive biopsy [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the sensitivity was significantly higher when both MMG and US were used for women with dense breasts (77.5%) than when MMG alone was used (50%) [ 30 ]. The J-START, a large randomized controlled trial conducted in Japan to examine the usefulness of adding US to MMG examinations for women in their 40s with a high prevalence of dense breasts [ 31 , 32 ], demonstrated that the combined use of US and MMG increased the rate of breast cancer detection by 1.5-fold, as compared with the use of MMG alone. Furthermore, the combined use of US resulted in increased sensitivity, regardless of breast density, indicating that combined US is the best method for these women.…”
Section: Discussionmentioning
confidence: 99%
“…Higher lesion stiffness corresponds to a greater probability of malignancy 72 . In clinical practice, US is used mainly for supplementary screening in women with dense breasts and negative mammogram findings, and for localizing lesions identified by mammography or MRI for puncture biopsy 73 , 74 .…”
Section: Imaging Techniques For Screening Breast Cancermentioning
confidence: 99%